Cervical disc arthroplasty combined with two‐level ACDF for the treatment of contiguous three‐level cervical degenerative disc disease: A comparative study. Issue 5 (13th September 2022) - Huang, Kangkang; Liu, Hao; Wang, Beiyu; Wu, Tingkui; Ding, Chen; He, Junbo; Meng, Yang; Wang, Han; Hong, Ying
Abstract: To compare the differences among constructs with one‐level cervical disc arthroplasty (CDA) and two‐level anterior cervical discectomy and fusion (ACDF). A retrospective study was conducted involving patients who underwent one‐level CDA and two‐level ACDF between June 2012 and July 2020. According to the different locations of CDA and ACDF, we divided the constructs into three types: type Ⅰa: CDA‐ACDF‐ACDF; type Ⅰb: ACDF‐CDA‐ACDF; type Ⅰc: ACDF‐ACDF‐CDA. The differences of clinical and radiological outcomes were evaluated. Fifty‐three patients were included with 29 in type Ⅰa group, 11 in type Ⅰb group, and 13 in type Ⅰc group. After surgery, all groups showed significant improvement in apanese Orthopedic Association, Neck Disability Index, and Visual Analog Scale scores ( p  < 0.001). Range of motion (ROM) of the total cervical spine in type Ⅰc group decreased significantly compared with those in type Ⅰa and type Ⅰb groups ( p  < 0.05). No significant differences in ROM of the arthroplasty segment and the variations in ROM of the superior adjacent segment were observed among the three groups. The fusion rates of the superior ACDF segments were significantly higher at 6 and 12 months postoperatively than those of the inferior ACDF segments ( p  < 0.05). The clinical outcomes were similar among constructs concerning different locations of CDA and ACDF in three‐level hybrid surgery. ROM of the cervical spine in type Ⅰc group decreased significantly compared with that in type Ⅰa and type Ⅰb groups. The fusion rates of superior ACDF segments were higher at early time points after surgery than those of inferior ACDF segments.